Assessing behavior and cognition in rodents, nonhuman primates, and humans: where are the limits of translation? . Issue 3 (30th September 2019) - Stephan, Marius; Volkmann, Paul; Rossner, Moritz J.
Abstract : New psychopharmacological treatments are needed for affective and nonaffective psychoses, especially for the associated negative and cognitive symptoms. Earlier developments mostly failed, probably partly because of limitations in behavioral models used for validation. Now, deeper understanding of the genetics underlying disease pathogenesis and progress in genetic engineering will generate many rodent models with increased construct validity. To improve these models' translational value, we need complementary data from nonhuman primates. We also have to improve and streamline behavioral test systems to cope with increased demand. Here, we propose a comprehensive neurocognitive test battery that should overcome the disadvantages of single tests and yield cognitive/behavioral profiles for modeling subsets of patient symptoms. Further, we delineate a concept for classifying disease-relevant cognitive endophenotypes to balance between face and construct validity and clinical diagnostics. In summary, this review discusses new concepts and the limitations and future potential of translational research on cognition in psychiatry.